2017
DOI: 10.2147/cia.s145688
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of two different respiratory training protocols in elderly patients with chronic obstructive pulmonary disease

Abstract: AimThe aim of the present study was to compare threshold inspiratory muscle training (IMT) and expiratory muscle training (EMT) in elderly male patients with moderate degree of COPD.Materials and methodsForty male patients with moderate degree of COPD were recruited for this study. They were randomly divided into two groups: the IMT group who received inspiratory training with an intensity ranging from 15% to 60% of their maximal inspiratory pressure, and the EMT group who received expiratory training with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 32 publications
2
22
0
11
Order By: Relevance
“…Two thousand and fifty‐seven articles were identified but only 43 studies (38 RCT, 2 CT, and 3 cohort studies) were included in the systematic review and 37 out of them in the meta‐analysis. Reasons for study exclusion are outlined in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Two thousand and fifty‐seven articles were identified but only 43 studies (38 RCT, 2 CT, and 3 cohort studies) were included in the systematic review and 37 out of them in the meta‐analysis. Reasons for study exclusion are outlined in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Lo anterior es enfatizado por Rodríguez, et al, quien presenta resultados similares en 20 mujeres AM, evidenciando una mejor capacidad aeróbica y retrasando la aparición de la fatiga (17) . La conclusión de estos autores es que al postergar la depleción de glucógeno, se pospone la fatiga, definiéndose ésta como "la incapacidad de seguir manteniendo una fuerza muscular apropiada al esfuerzo, llevando a disminuir la performance del sujeto" (18) . Este concepto de fatiga en la musculatura respiratoria está ligado a procesos de activación de los mecanorreceptores y el metabolorreflejo.…”
Section: Discussionunclassified
“…Esto concuerda con una investigación en animales donde se demostró que se puede consumir más lactato en ejercicio intenso, llevando así a una mayor metabolización de este sustrato, y por lo tanto disminuyendo su concentración en sangre. Resultados similares fueron obtenidos por Mehani (18) , argumentando una disminución del metabolorreflejo, atenuando el fenómeno de vasoconstricción en los músculos de las extremidades inferiores.…”
Section: Discussionunclassified
“…All studies found that pulmonary rehabilitation programs or individual physical therapy programs were effective in improving the quality of life [12][13][14][15][16][17], physical endurance [12][13][14][15][16][18][19][20][21][22][23], respiratory muscle strength [13,18,23], reducing symptoms of CoPd [14,16,19,23], improving the function of external breathing [16,[24][25][26], blood parameters [22,27], cognitive functions [21], functional state of muscles [28], survival rates [29,30], and reducing the number of hospital days [31]. The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd.…”
Section: Resultsmentioning
confidence: 99%